Development of a Questionnaire to Determine Incidence and Attitudes to "Voluntary Stopping of Eating and Drinking" - Sabrina Stängle MS; Wilfried Schnepp PhD; Mirjam Mezger PhD; Daniel Büche MD; André Fringer PhD (SAGE Publishing, 2019)
Background "Voluntary stopping of eating and drinking" (VSED) is an option to hasten death at the end of life. There are no data available about incidence of either the explicit VSED or implicit (V)SED nor information about experiences and attitudes of health professionals about VSED in Switzerland. Aims To develop, test, and translate a standardized questionnaire that measures the incidence of VSED, and physicians' and nurses' experiences about explicit VSED and implicit (V)SED. Methods The development of the questionnaire was based on a systematic search, which were updated in 2016. The questionnaire was tested by palliative care specialists using standard pretest and content validity index (CVI). Subsequently, a forward/backward translation was made. Results The questionnaire includes 38 items. Feedback of 15 participants in the standard pretest were positive in terms of intelligibility with an average time of 28 minutes. After adjustment, 27 experts validated the items in two rounds. The questionnaire achieves excellent item-CVI values between 0.91 and 1.00 and scale-CVI values of 0.97. The forward/backward translations were each carried out by two independent translators with subsequent building of a consensus through a consultant. Conclusion A mulitlingual questionnaire has been developed, which measures the incidence of explicit VSED and implicit (V)SED. This questionnaire is the basis for a Swiss-wide census of all physicians and nurses of outpatient and long-term care.